「轉念一想，綻放光芒」國小二年級實施樂觀課程之行動研究 An Action Research of Implementing Optimism Program in the Second Grades of Elementary School - 丘愛鈴Ai-Ling Chiu; 黃郁婷Yu-Ting Huang (Higher Education Foundation, 2009)
本研究旨在依據正向心理學的解釋風格理論，發展適合國小二年級的樂觀課程，分析樂觀課程實施的歷程與遭遇困境，探討實施樂觀課程後學童的改變與成長。本研究採行動研究，以高雄縣某公立國小二年級27位學童為研究參與者，在綜合活動學習領域實施八節樂觀課程，以觀察、訪談、文件分析等方法進行資料蒐集與分析。研究發現：一、以學童生活事件或親身經驗為教材，能引起學習動機；二、多元化教學策略以「體驗學習」、「讚美和分享」最受學童喜愛；三、「六頂思考帽」口訣能引導學童聚焦思考；四、學童能運用「樂觀秘笈」改變想法和調整情緒，但問題解決行動有待加強；五、書寫「情緒日誌」，有助於學童自我省思與實踐。最後，根據研究發現，提出若干建議，提供國小教師實施樂觀課程與教學之參考。 This study aims to achieve three purposes: (1) To develop optimism program which is suitable for the second grades of the elementary school. (2) To analyze the process and difficulties of carrying out the optimism program. (3) To discuss the students' change and growth after implementing the optimism program. This study adopts action research. There are 27 students participate in this study and the data collected include instructional diary of classroom observation, children's performances and learning records, and interviews. The conclusions are as follows: (1) Teaching materials which are close to the students' experience of daily life or their personal experience could arouse the schoolchild learning motivation. (2) Among multiple teaching strategies, "experience learning" and "praises and shares" are the most popular for students. (3) The application of "six thinking hats" could help pupils to concentrate on thinking. (4) The students can use the ways of "optimistic secrets" to change negative ideas and adjust their emotions, but the effect of solving problems leaves some room to improve. (5) Writing "emotional journal" is helpful to let students thinking about themselves and practice. Finally, based on the conclusions mentioned above, the authors propose some suggestions for elemental school teachers to improve their curriculum design and implementation of optimism program in their teaching.